Bagaimana Literasi Kewirausahaan dan Literasi Digital Berpengaruh terhadap Keberlanjutan Usaha Pedagang Pakaian? - Nur Asni Aulia; Muhammad Hasan; Muhammad Dinar; M. Ihsan Said Ahmad; Tuti Supatminingsih (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
Writing this thesis aims to determine the sustainability of the clothing merchant business in the Baru market, Bantaeng Regency, by focusing on three variables, namely entrepreneurial literacy, digital literacy and business sustainability in 3 respondents as the research sample. This study uses qualitative methods, using data collection techniques with interviews, direct observation of the object of research. Then the research results were assessed using a qualitative approach technique. The data collection techniques above obtained the results of research showing that entrepreneurial literacy and digital literacy of clothing traders in the Baru market, Bantaeng Regency, can be categorized as good enough to support the development of these clothing traders. This is because traders have an understanding of the business they have established, never neglect in carrying out their obligations and things that can interfere with the existence of the business. Meanwhile, business continuity shows that the clothing merchant business in New Market, Bantaeng Regency, can be categorized as quite good, because it can develop well.